2015
DOI: 10.1111/hpb.12452
|View full text |Cite
|
Sign up to set email alerts
|

Understanding drivers of hospital charge variation for episodes of care among patients undergoing hepatopancreatobiliary surgery

Abstract: After accounting for in-hospital complications, the total mean hospital charges for HPB surgery remained variable by case type and provider. While the variation in charges was associated with LOS, provider-level differences in across-the-board charges were also noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Consistent with previous reports, 26,27 data from the present study noted that higher patient comorbidity, extended length of stay, and nonroutine discharge were associated with higher costs and charges. Furthermore, the occurrence of an inpatient complication was associated with a 10% to 45% increase in the cost and charge.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports, 26,27 data from the present study noted that higher patient comorbidity, extended length of stay, and nonroutine discharge were associated with higher costs and charges. Furthermore, the occurrence of an inpatient complication was associated with a 10% to 45% increase in the cost and charge.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, significant variation existed among surgeons performing similar resection types. Although not specifically addressed in this study, a previous report 24 found that variations in LOS and operating room, laboratory, radiology, and supply costs were the main drivers of this variation. As such, further studies should be conducted to identify and potentially target unnecessary spending and consequently improve health care quality and value.…”
Section: Discussionmentioning
confidence: 79%
“…9,10 In addition, HPB complications can be relatively resource intensive and generate costs greater than complications associated with general surgical cases. 11 The economic impact associated with the perioperative morbidity and mortality following HPB surgery remains, however, poorly defined. [12][13][14][15] No study to date has specifically evaluated Medicare payments associated with complications, rescue, or failure to rescue (FTR) among patients undergoing HPB operations.…”
Section: Introductionmentioning
confidence: 99%